PENINGKATAN HASIL BELAJAR MATERI KOSAKATA KATA SIFAT, SINONIM DAN ANTONIM MELALUI MEDIA WEBSITE WORDSEARCH PADA PESERTA DIDIK KELAS V UPT SD NEGERI 067241 MEDAN DENAI DENGAN MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) - Rena Maharani Ashari; M Fauzi Hasibuan; Syafrida Ernayanti (STKIP Subang, 2024)
This study aims to thoroughly examine and systematically enhance the vocabulary learning outcomes in adjectives, synonyms, and antonyms through the utilization of the WordSearch website for Grade V students at UPT SD Negeri 067241 Medan Denai by implementing the Team Game Tournament (TGT) model. The TGT model includes five stages: class presentation, team learning, games, tournament, and team recognition. The research employs Classroom Action Research (CAR) with four stages: planning, action, observation, and reflection. Data were collected through pre-tests, post-tests after cycle 1, and post-tests after cycle 2. The findings reveal significant improvements in learning outcomes, with the percentage of students achieving the Kriteria Ketuntasan Tujuan Pembelajaran (KKTP) increasing from 44% in the pre-test to 85.19% in the post-test cycle 2. The results show that the implementation of the TGT model effectively enhances vocabulary learning outcomes.